Antibodies to unknown antigens other than swine leukocyte antigens on GTKO/β4GalNT2KO pig cells are associated with AHXR after pig-to-rhesus monkey kidney transplantation - Jiang, Hongtao; Jiang, Haiyun; He, Songzhe; Chen, Yuxiang; Du, Jiaxiang; Pan, Dengke; Li, Tao; Wang, Yi (Frontiers in Immunology, 2025)
BackgroundAlthough progress in experimental life-supporting pig renal xenotransplantation has been encouraging, acute humoral xenograft rejection (AHXR) is still an obstacle to the survival of non-human primates that received genetically modified pig kidneys. This is possibly associated with the expression of xenoantigens in addition to the two known xenoantigens (Gal and Sda). We attempted to clarify the effect of elicited antibodies on GTKO/β4GalNT2KO-based pig-to-rhesus monkey renal xenotransplantation.MethodsRhesus monkeys (n = 7) received kidneys from GTKO/β4GalNT2KO (n = 1) or GTKO/β4GalNT2KO/hCD55/hTBM (n = 3) pigs, and recipient serum was collected. Serum was incubated with GTKO/β4GalNT2KO pig red blood cells (pRBCs) to measure remaining antibodies to pig peripheral blood mononuclear cells (pPBMCs). Antibody binding and cytotoxicity of serum (either adsorbed on pig RBCs or unabsorbed) to GTKO/β4GalNT2KO or GTKO/β4GalNT2KO/hCD55/hTBM pig PBMCs or RBCs were measured by flow cytometry. At biopsy or euthanasia, the grafts were examined by histological assessment.ResultsSurvival of the seven recipients was <30 days. Serum creatinine was increased, and platelet count was decreased. Anti-pig antibodies (IgG or IgM) were elevated in the serum of all seven recipients at some time point. Histopathology of the kidneys showed features of AHXR and thrombotic microangiopathy in all grafts. Immunohistochemistry showed C3c, C4d, IgM and/or IgG, and C5b-9 deposition and CD68 infiltration in most grafts. Serum anti-pig antibodies remained elevated even after absorption on pig RBCs, which indicated that another xenoantigen, e.g., swine leukocyte antigens (SLAs) or “neoantigen I” (which also expresses on pig PBMCs but does not express on pig RBCs), may be playing a role in AHXR. Neoantigen I is an unidentified xenoantigen expressed on PBMCs, shared with kidney xenografts but not present on RBCs. There was a difference in antibody binding to PBMCs between unabsorbed and absorbed serum, suggesting the presence of anti-”neoantigen II” (which is expressed on pig RBCs and PBMCs) antibodies on PBMCs, which may be important in causing AHXR.ConclusionsThese data suggest that elicited antibodies to “neoantigens”, e.g., non-SLA, play a role in AHXR after GTKO/β4GalNT2KO-based pig kidney transplantation in non-human primates.